Triptolide enhances carboplatin-induced apoptosis by inhibiting nucleotide excision repair (NER) activity in melanoma - Wang, Geng; Guo, Hongmin; Ren, Yan; Chen, Weiyi; Wang, Yixuan; Li, Jianing; Liu, Hua; Xing, Jingjun; Zhang, Yanru; Li, Na (Frontiers in Pharmacology, 2023)
Carboplatin (CBP) is a DNA damaging drug used to treat various cancers, including advanced melanoma. Yet we still face low response rates and short survival due to resistance. Triptolide (TPL) is considered to have multifunctional antitumor effects and has been confirmed to enhance the cytotoxic effects of chemotherapeutic drugs. Herein, we aimed to investigate the knowledge about the effects and mechanisms for the combined application of TPL and CBP against melanoma. Melanoma cell lines and xenograft mouse model were used to uncover the antitumor effects and the underlying molecular mechanisms of the alone or combined treatment of TPL and CBP in melanoma. Cell viability, migration, invasion, apoptosis, and DNA damage were detected by conventional methods. The rate-limiting proteins of the NER pathway were quantitated using PCR and Western blot. Fluorescent reporter plasmids were used to test the NER repair capacity. Our results showed that the presence of TPL in CBP treatment could selectively inhibit NER pathway activity, and TPL exerts a synergistic effect with CBP to inhibit viability, migration, invasion, and induce apoptosis of A375 and B16 cells. Moreover, combined treatment with TPL and CBP significantly inhibited tumor progression in nude mice by suppressing cell proliferation and inducing apoptosis. Together, this study reveals the NER inhibitor TPL which has great potential in treating melanoma, either alone or in combination with CBP.